DIGITAL ACCOUNTING EDUCATION THROUGH THE AKUNTANSIKUAPPLICATION FOR MSMEsCV ASA MANDIRI & PT GESANG SEMPULUR MIGUNANI - Berlian Amalia Ramadhani (Jurnal Pengabdian Masyarakat, 2024)
Financial reports play a vital role in a business as they are used to record all expenses andrevenues. Additionally, financial reports serve to determine the extent of profit or earningsobtained. These financial reports serve as the foundation for crafting strategies and makingbusiness-related decisions. The aim of this activity is to provide training and guidance onfinancial transaction recording for CV Asa Mandiri and PT Gesang Sempulur Migunani.Currently, these small and medium-sized enterprises (UMKM) manually record their financialtransactions, and they blend personal and company finances, making it challenging for businessowners to ascertain their profits. This difficulty arises from the owners' limited understanding ofthe fundamental principles of financial transaction recording and the significance of financialreporting. Hence, this training and mentoring activity is being carried out to assist CV AsaMandiri and PT Gesang Sempulur Migunani in enhancing their financial transaction recordingpractices.